2021
DOI: 10.3390/ijerph18020769
|View full text |Cite
|
Sign up to set email alerts
|

Stress/Immune Biomarkers in Saliva among Children with ADHD Status

Abstract: Background. This cross-sectional study aimed to evaluate stress and immune biomarkers in saliva samples of attention-deficit/hyperactivity disorder ADHD compared to healthy non-ADHD children. Material and methods. A total of 132 children under 11 years old (8.5 ± 1.1) enrolled in a cross-sectional study: with confirmed ADHD (n = 60) and healthy controls (n = 72). The clinical evaluation included physical measurements (height, waist, hip circumference, body weight, body mass index BMI, BMI z-score) and unstimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A recent study concluded that saliva can be used to monitor ADHD status with regard to biomarkers that indicate the hypothalamus-pituitary-adrenal axis and sympathetic activity [48]. Furthermore, as previously mentioned, ADHD is associated with a higher occurrence of autoimmune and inflammatory conditions [23].…”
Section: Resultsmentioning
confidence: 97%
“…A recent study concluded that saliva can be used to monitor ADHD status with regard to biomarkers that indicate the hypothalamus-pituitary-adrenal axis and sympathetic activity [48]. Furthermore, as previously mentioned, ADHD is associated with a higher occurrence of autoimmune and inflammatory conditions [23].…”
Section: Resultsmentioning
confidence: 97%
“…One possibility is that the immune and inflammatory changes associated with ADHD may be associated with a reduced likelihood of infection. These changes include lower levels of cortisol, elevated levels of interleukin-6 (IL-6) and C-reactive protein (CRP), and reduced levels of tumor necrosis factor alpha (TNF-α) in children and adolescents (Chang et al, 2020(Chang et al, , 2021Elsadek et al, 2020;Krahel et al, 2021), though these findings have not been consistent in adult patients (de Jong et al, 2016). The association with IL-6 is of particular interest, because genetic variants affecting the expression of IL-6 have been associated with variations in cross-national prevalence of COVID-19 (Karcioglu Batur & Hekim, Dongen et al, 2019), this hypothesis merits further investigation, as it may explain the finding of a possible "protective" effect (Arbel et al, 2020) despite the higher likelihood of "risky" behaviors in persons with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in two recent reports which found that the presence of ADHD symptoms was associated with an increased likelihood of non-adherence to safety measures (Pollak et al, 2021a, 2021b). ADHD has also been associated with alterations in immune and inflammatory activity, such as elevated or decreased levels of particular inflammatory mediators (Anand et al, 2017; Chang et al, 2020, 2021; Krahel et al, 2021). It is not clear if these changes have a beneficial or harmful effect in individuals with SARS-CoV-2 infection (Yonas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A single saliva or blood test at rest can evaluate baseline levels of peripheral markers of inflammation and/or the state of hormonal pathways that modulate immune and inflammatory systems [60,61], such as the sympathetic-adrenal-medullary (SAM) system and the hypothalamic-pituitary-adrenal (HPA) axis (for a review, see [62,63]). Peripheral markers of inflammation include, for example, anti-inflammatory (such as IL4, IL5, IL10, transforming growth factor-β [TGF-β], C-C motif chemokine ligand-14) and pro-inflammatory (IL1, IL2, IL6, IL8, IL12, TNF-α, interferon-gamma, monocyte chemoattractant protein-1 [MCP1]) chemokines and cytokines, their receptors (e.g., soluble TNF-receptor-1 [sTNF-R1]), acutephase proteins, blood immune cells, complement system components and antibodies.…”
Section: Measures Of Inflammation In Psychiatric Patientsmentioning
confidence: 99%